Pengembangan Alat Peraga Efek Rumah Kaca Untuk Menumbuhkan Keterampilan Proses Sains Siswa SMP Kelas VII Pada Tema Pemanasan Global - Yulianah, Yulianah; Leksono, Suroso Mukti; El Islami, R. Ahmad Zaky (UNIB Press, 2025)
The purpose of this research is to create a greenhouse effect teaching tool in science learning on the themeof global warming to foster Science Process Skills (PPP) in students. The development model used is a 4-D development model which consists of four stages: define, design, develop, and disseminate. Productvalidation was carried out by science education experts and practitioner experts who showed the level ofproduct validity with a value of 86.18% included in the